Non‐Val30Met mutation, septal hypertrophy, and cardiac denervation in patients with mutant transthyretin amyloidosis. (4th October 2018) - Hirakawa, Kyoko; Takashio, Seiji; Marume, Kyohei; Yamamoto, Masahiro; Hanatani, Shinsuke; Yamamoto, Eiichiro; Sakamoto, Kenji; Izumiya, Yasuhiro; Kaikita, Koichi; Oda, Seitaro; Utsunomiya, Daisuke; Shiraishi, Shinya; et al.
Abstract: Aims: Mutant transthyretin (ATTRm) amyloidosis is a systemic disease caused by the deposition of amyloid fibrils derived from mutated transthyretin. Although cardiac involvement impacts the prognosis of patients with ATTRm amyloidosis, the incidence of cardiac events, such as bradyarrhythmia, ventricular tachycardia, and heart failure, has not been fully elucidated. The aim of this study was to evaluate the prognosis and predictors of clinical outcomes, including cardiac events, in patients with ATTRm amyloidosis in Japan. Methods and results: We evaluated 90 consecutive patients with ATTRm amyloidosis at Kumamoto University. ATTRm amyloidosis was diagnosed by the observation of both amyloid fibril deposition on tissue biopsy and a transthyretin mutation on sequential analysis. Sympathetic nerve activity was evaluated in 59 patients using 123‐iodine metaiodobenzylguanidine ( 123 I‐MIBG) imaging. The endpoint was a composite of all‐cause death, hospitalization for heart failure, and implantation of a pacemaker, implantable cardioverter defibrillator, or cardiac resynchronization therapy defibrillator. Sixty‐seven patients had the Val30Met mutation (74%). The composite endpoint occurred in 23 patients (26%): all‐cause death ( n  = 6), hospitalization for worsening heart failure ( n  = 1), and implantation of an implantable cardioverter defibrillator ( n  = 6), cardiac resynchronization therapy defibrillator ( n  = 3), or pacemaker ( n  = 7). The 5‐year incident rate for clinical outcomes was 19%. In a multivariate Cox hazard analysis, age [hazard ratio (HR): 1.07, 95% confidence interval (95% CI): 1.01–1.12, P  = 0.015], PQ interval (HR: 1.01, 95% CI: 1.00–1.02, P  = 0.042), interventricular septum thickness in diastole (HR: 1.25, 95% CI: 1.09–1.42, P  = 0.001), and non‐Val30Met mutation (HR: 4.31, 95% CI: 1.53–12.16, P  = 0.006) were independent predictive factors of clinical outcomes. Kaplan–Meier analysis demonstrated a significantly higher probability of the composite endpoint in the non‐Val30Met group than in the Val30Met group (log‐rank test: P  = 0.002) and in patients with left ventricular hypertrophy than in patients without left ventricular hypertrophy (log‐rank test: P  < 0.001). In patients who underwent 123 I‐MIBG imaging, a delayed heart‐to‐mediastinum (HM) ratio <1.6 was a significant predictive factor of the composite endpoint (HR: 4.98, 95% CI: 1.73–14.37, P  = 0.003) in the univariate Cox hazard analyses. Kaplan–Meier curve analysis showed that a delayed HM ratio <1.6 was associated with a poor prognosis (log‐rank test: P  = 0.001). Conclusions: Non‐Val30Met mutation, septal hypertrophy, and a delayed HM ratio are useful predictors of clinical outcomes in patients with ATTRm amyloidosis in Japan. These results suggest that it is important to evaluate cardiac involvement in terms of morphological (left ventricular hypertrophy) and functional (cardiac denervation) perspectives using echocardiography and 123 I‐MIBG imaging, respectively.